Redesain Instalasi Pengolahan Air Limbah (IPAL) dengan Penambahan Unit Biodigester Skala Komunal Kapasitas 5 m3 - Muhammad Qarinur; Wisnu Prayogo; Tri Rahayu; Laili Fitria (Universitas Tanjungpura, 2022)
IPAL as a wastewater treatment facility from MCK activities in Sindangsari Village has been managed by KSM Amanah since 2013 and is still operating today. This WWTP accepts domestic waste input of 14,656 m3/day from 50 house connections and communal toilets with a total of 200-230 users per day. The management unit in the WWTP uses the DEWATS system which is equipped with a settler, biodigester, and ABR as a multilevel sedimentation and filtration tank. Communal MCK consists of 5 bathrooms and 1 operational room which is still functioning today. The condition of ABR is already filled with mud and there is a lot of garbage in it, so this condition can reduce the effectiveness of the existing WWTPs. For this reason, the domestic liquid waste produced must go through several processing stages so that the content of domestic liquid waste that will be disposed of to the environment is safe or can even be reused and as much as possible provides additional benefits in the form of biogas. The purpose of this study is to evaluate the domestic WWTP used and compare it with the domestic wastewater quality standards listed in the Minister of Environment and Forestry Regulation No. 68 of 2016. In addition, to maintain the MCK facilities that have been built, it is necessary to provide SOP guidance for both users and managers. Keywords: WWTP; DEWATS; domestic waste Abstrak IPAL sebagai fasilitas pengolahan air limbah dari aktivitas MCK di Kelurahan Sindangsari dikelola oleh KSM Amanah sejak tahun 2013 dan masih beroperasi sampai saat ini. IPAL ini menerima masukan limbah domestik sebesar 14,656 m3/hari dari 50 sambungan rumah dan MCK Komunal dengan total pengguna sebanyak 200-230 orang per hari. Unit pengelolaan yang terdapat pada IPAL menggunakan sistem DEWATS yang dilengkapi bak settler (pengendap), biodigester, dan ABR sebagai bak pengendapan bertingkat dan penyaringan. MCK Komunal terdiri dari 5 kamar mandi dan 1 ruang operasional yang masih berfungsi sampai saat ini. Kondisi ABR sudah dipenuhi lumpur dan terdapat banyak sampah di dalamnya sehingga kondisi ini dapat mengurangi efektivitas IPAL yang sudah ada. Untuk itu, limbah cair domestik yang dihasilkan harus melalui beberapa tahapan pengolahan agar kandungan limbah cair domestik yang akan dibuang ke lingkungan aman atau bahkan dapat dimanfaatkan kembali serta sebisa mungkin memberikan manfaat tambahan berupa biogas. Tujuan dari penelitian ini sehingga untuk mengevaluasi IPAL domestik yang digunakan dan dibandingkan dengan baku mutu air limbah domestik yang tercantum pada Permen LHK No. 68 tahun 2016. Selain itu, untuk menjaga fasilitas MCK yang sudah dibangun, perlu diberikan pengarahan SOP baik bagi pengguna dan juga pengelola. Kata Kunci: IPAL, DEWATS, limbah domestik, biogas.